A switch in time : a new strategy for America in Iraq - Pollack, Kenneth M. (Kenneth Michael), 1966- (Analysis paper (Brookings Institution. Saban Center for Middle East Policy), 2006)
There is no greater foreign policy challenge for the United States today than the reconstruction of Iraq. For this reason, in November-December 2005, the Saban Center for Middle East Policy at the Brookings Institution brought together a small group of experts on Iraq, on the process of political and economic reconstruction, and on military affairs, under the direction of its Director of Research, Kenneth M. Pollack, to consider U.S. policy toward Iraq in all of its dimensions. Pollack then took the fruits of these discussions, along with findings from trips to Iraq and to U.S. Central Command headquarters in Tampa, and crafted them into a new report from the Saban Center entitled A Switch in Time: A New Strategy for America in Iraq. This monograph details a comprehensive, alternative approach to current U.S. military, political, and economic policies in Iraq.